ASSESSING THE USE OF GEOSPATIAL TECHNOLOGIES IN HIGHER EDUCATION TEACHING - Nicholas Wise (European Journal of Geography)
Educators continually seek new technologies to complement and enhance the student learning experience. The use of technologies in the classroom promotes spatial awareness, important across a number of disciplines. To better enable students to gain spatial awareness, higher education educators creatively utilise geospatial technologies in the classroom to enhance engagement and help visualise theoretical subject content. Teaching innovations and integrating technologies into the classroom over the past decade adhere to changing technological paradigms aimed at better engaging students in lectures and seminars to increase their practical and applied understanding and make classes more interactive. This study is an analysis of insight on approaches observed in academic literature. Three these themes emerged and are articulated in this paper: classroom engagement, interactive spatial knowledge, and practical skills acquisition. The first two are concerned with learning impacts in the classroom whilst the third theme focuses on career impacts.